Padlet Application-Based Media on Many Facets Building Materials:: Learning Media Innovation for Elementary Schools - Richo Budi Santoso; Bahauddin Azmy; Via Yustitia (Universitas Sarjanawiyata Tamansiswa, 2022)
This research is motivated by the needs of educators at SD Negeri Kepuh Kiriman 1 where educators need distance learning media that can group learners' answers and not make educator storage memory full quickly. The purpose of this development research is to describe the development process. This study uses a type of Reseacrh and Development (R&D) research. This development research is adapted from the ADDIE development model (Analize, Design, Develop, Implementation, and Evaluation), but is limited to the development stage. Data collection methods use documentation and questionnaires. The data analysis techniques used in this study use descriptive analysis to describe quantitative processes and analysis to determine product feasibility. The results showed that the product was developed through three stages, namely the Analysis stage (it takes a virtual distance learning media without a virtual face-to-face that can provide a concrete picture for class IV learners), Design (in the form of an initial framework in which it contains the content and content of Padlet digital learning media), Development (in the form of products resulting from the development of padlet application-based learning media on many facets of building materials).